Effects of a Single Escape Mutation on T Cell and HIV-1 Co-adaptation - Sun, Xiaoming; Shi, Yi; Akahoshi, Tomohiro; Fujiwara, Mamoru; Gatanaga, Hiroyuki; Schönbach, Christian; Kuse, Nozomi; Appay, Victor; Gao, George F.; Oka, Shinichi; Takiguchi, Masafumi (Cell Reports, 2016)
Summary The mechanistic basis for the progressive accumulation of Y135F Nef mutant viruses in the HIV-1-infected population remains poorly understood. Y135F viruses carry the 2F mutation within RW8 and RF10, which are two HLA-A∗24:02-restricted superimposed Nef epitopes recognized by distinct and adaptable CD8+ T cell responses. We combined comprehensive analysis of the T cell receptor repertoire and cross-reactive potential of wild-type or 2F RW8- and RF10-specific CD8+ T cells with peptide-MHC complex stability and crystal structure studies. We find that, by affecting direct and water-mediated hydrogen bond networks within the peptide-MHC complex, the 2F mutation reduces both TCR and HLA binding. This suggests an advantage underlying the evolution of the 2F variant with decreased CD8+ T cell efficacy. Our study provides a refined understanding of HIV-1 and CD8+ T cell co-adaptation at the population level.